Conducting the Needs Assessment #1: Introduction - Matthew Benge; Amy Harder; Laura Warner (EDIS, 2019)
An integral step in the program development process is identifying the needs of a community. Educators seeking to develop and deliver an educational program must first be informed of what their audience lacks in order to develop the right curriculum or training. This initial publication in the Conducting the Needs Assessment series provides a brief introduction to the planning, implementation, and prioritization of needs within a community or specific clientele group. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Matthew Benge, Amy Harder, and Laura Warner. https://edis.ifas.ufl.edu/wc340